2012
DOI: 10.3109/00016357.2012.697577
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of health complaints before and after removal of amalgam fillings — 3-year follow-up

Abstract: The inter-individual variation of intensities of health complaints was considerable and the reduction of health complaints varied for the different complaints. Several factors may be of importance for the observed reduction of complaint intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The most commonly reported single symptoms in this study were tendency to rapid exhaustion followed by tiredness , concentration disturbance , and pain in joints and limps . This finding is in line with other Scandinavian studies in similar populations [ 12 , 13 , 24 ]. Lygre et al [ 12 ] found that the most reported complaints were local symptoms around the mouth and general complaints such as pain from muscles and joints, fatigue and memory disturbance - a symptom pattern, which is confirmed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…The most commonly reported single symptoms in this study were tendency to rapid exhaustion followed by tiredness , concentration disturbance , and pain in joints and limps . This finding is in line with other Scandinavian studies in similar populations [ 12 , 13 , 24 ]. Lygre et al [ 12 ] found that the most reported complaints were local symptoms around the mouth and general complaints such as pain from muscles and joints, fatigue and memory disturbance - a symptom pattern, which is confirmed in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Our results add to the body of evidence that there is reduced likelihood of health complaints after removal of the amalgam fillings, consisting of either a decrease of subjective symptom burden overall or subtle effects on symptoms, mood, motor function (hand steadiness) and cognition [ 42 , 45 – 50 ]. Our findings suggest that there remains increased risk of health deterioration in study participants even with mercury levels below the established HBM-I no risk urine mercury value.…”
Section: Discussionmentioning
confidence: 51%
“…The possible dose–response relationship between low-level mercury vapor exposure and subclinical neurological and psychological effects has been characterized previously as preclinical symptoms (predominantly in dentists and dental assistants) [ 17 , 51 , 56 ]. Symptom changes associated with amalgam removal have been seen in other studies and include a diverse range of adverse effects including decreased motor functioning (e.g., losses in hand steadiness and manual dexterity, progressing to incoordination, imbalance and tremor in muscles that perform fine motor control) and loss of mental capacity (e.g., memory, confusion, diminished logical reasoning and concentration) [ 42 , 45 , 47 , 50 ]. Most of these studies are limited by their small sample size (amalgam removal group sample sizes of 20, 20, 60 and 796 respectively with the latter being a retrospective study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study protocol was developed by a task group appointed by the Amalgam-attributed health complaints are heterogeneous and a variety of symptoms has been attributed to amalgam. [13][14][15][16][17] Since the symptom pattern is unspecific, amalgam-attributed health complaints are difficult to validate and are, for the most part, quantified using symptom scales. Notably, amalgam-attributed health complaints are largely similar to complaints experienced by patients with so-called 'medically unexplained physical symptoms' (MUPS) 18,19 or 'medically unexplained symptoms' (MUS).…”
Section: Introductionmentioning
confidence: 99%